Habituation Educational Values in Ethnoparenting of Penrek Tojang Traditional Ceremony of the Bugis Tribe : A Study of Transcendental Phenomenology - Dhea Adela; I Wayan Lasmawan; I Wayan Kertih (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study aims to reveal educational value contained in the ethnoparenting of Penrek Tojang of the Bugis Tribe in Wattang Sidenreng, Sidenren Rappang Regency. This study used a qualitative approach with a type of transcendental phenomenology. The subjects in this study were a pair of parents (father and mother) who had carried out the Penrek Tojang ceremony at the birth of their child. Data collection techniques were carried out using semi-structured interviews, observation, and documentation, until it reached the stage of exploring intention and eidetic reduction (values/ideas) which underlies pure subjectivity. The core processes of this research were epoche, reduction, imaginative variation, and synthesis of meanings and essence. The analysis technique used epoche/bracketing. The results of the study showed that the implementation of ethnic-based parenting in ethnoparenting was still carried out through the Penrek Tojang event or the swing ride. The aim of the Penrek Tojang tradition is to get closer to Allah SWT and as a form of gratitude for having been given a child and asking for the child's safety. The implementation of Penrek Tojang began with the preparatory stage, namely preparing tools and materials as well as food to be served at the event. Then the event began with welcoming the invited guests, the process of throwing away, reading barazanji/makkulawi, cutting hair, kissing the baby, riding on a swing (menrek tojang), then closing with prayer and eating together. The educational values contained in ethnoparenting at the Penrek Tojang event include aqidah values, worship values, and moral values, namely the values of gratitude, politeness, affection, hospitality and helping. This is an effort to instill character education in children which makes them dignified in their lives and implies instilling life skills, including spiritual, emotional, and social skills.